Convergence to self-similarity in an addition model with power-like time-dependent input of monomers - Costa, Fernando Pestana da (2011)
In this note we extend the results published in Ref. 1 to a coagulation system with Becker-Doring type interactions and time-dependent input of monomers $J_{1}(t)$ of power–like type: $J_{1}(t)/(α t^{ω }) → 1$ as $t → ∞$, with $α > 0$ and $ω > − \frac{1}{2}$. The general framework of the proof follows Ref. 1 but a different strategy is needed at a number of points.